Growth response of mixed mediterranean oak coppices to rainfall reduction - Cotillas, Miriam; Sabaté, Santi; Gracia, Carlos; Espelta, Josep Mª (Forest Ecology and Management, 2009)
Climate change is one of the major challenges for ecosystem conservation. One of the most vulnerable areas to climate change is the Mediterranean Basin which is expected to suffer important changes in temperature and precipitation in the next few decades, leading to a warmer and dryer climate. Therefore, it is necessary to determine species-speciﬁc responses to increased drought to predict possible future changes in the structure and composition of Mediterranean forests, as well as to identify appropriate management strategies to mitigate these effects. The main aim of this study has been to experimentally simulate the effects of a 15% reduction in annual rainfall on the survival and growth of two co-occurring Mediterranean oaks with contrasting leafhabit (the evergreen Quercus ilex spp. ilex and the winter-deciduous Quercus cerrioides) and, to assess whether traditional selective thinning carried out in these mixed oak coppices (i.e. selection of one to few stems per stump) can modify the consequences of rainfall reduction. Soil moisture decreased under the rainfall reduction level while it increased in the thinned plots. Reduced rainfall did not inﬂuence tree mortality, but did lead to species-speciﬁc effects on height growth: no changes were observed in Q. ilex while height growth rate of Q. cerrioides decreased (c.a. 20%). Selective thinning improved tree growth (c.a. 50%) in stands both under natural and, and to a lesser extent, under reduced rainfall conditions. Nevertheless, the positive effects of thinning rapidly declined during our three years experiment, probably because the vigorous resprouting of thinned stumps. Our results show that the forecasted reduction in annual rainfall for the Western Mediterranean Basin can constrain the growth of some deciduous oaks in mixed oak coppices. Traditional selective thinning can increase soil moisture and encourage tree growth, thus partially mitigating this effect. However, the transient results observed in this experiment suggest the need to reconsider the intensity and the frequency of this traditional management practice in light of new climatic scenarios
Keywords: climate change; Drought; Forest management; Quercus cerrioides; Quercus ilex; resprouting

Growth response of mixed mediterranean oak coppices to rainfall reduction - Cotillas, Miriam; Sabaté, Santi; Gracia, Carlos; Espelta, Josep Mª (Forest Ecology and Management, 2009)
Climate change is one of the major challenges for ecosystem conservation. One of the most vulnerable areas to climate change is the Mediterranean Basin which is expected to suffer important changes in temperature and precipitation in the next few decades, leading to a warmer and dryer climate. Therefore, it is necessary to determine species-speciﬁc responses to increased drought to predict possible future changes in the structure and composition of Mediterranean forests, as well as to identify appropriate management strategies to mitigate these effects. The main aim of this study has been to experimentally simulate the effects of a 15% reduction in annual rainfall on the survival and growth of two co-occurring Mediterranean oaks with contrasting leafhabit (the evergreen Quercus ilex spp. ilex and the winter-deciduous Quercus cerrioides) and, to assess whether traditional selective thinning carried out in these mixed oak coppices (i.e. selection of one to few stems per stump) can modify the consequences of rainfall reduction. Soil moisture decreased under the rainfall reduction level while it increased in the thinned plots. Reduced rainfall did not inﬂuence tree mortality, but did lead to species-speciﬁc effects on height growth: no changes were observed in Q. ilex while height growth rate of Q. cerrioides decreased (c.a. 20%). Selective thinning improved tree growth (c.a. 50%) in stands both under natural and, and to a lesser extent, under reduced rainfall conditions. Nevertheless, the positive effects of thinning rapidly declined during our three years experiment, probably because the vigorous resprouting of thinned stumps. Our results show that the forecasted reduction in annual rainfall for the Western Mediterranean Basin can constrain the growth of some deciduous oaks in mixed oak coppices. Traditional selective thinning can increase soil moisture and encourage tree growth, thus partially mitigating this effect. However, the transient results observed in this experiment suggest the need to reconsider the intensity and the frequency of this traditional management practice in light of new climatic scenarios
Keywords: climate change; Drought; Forest management; Quercus cerrioides; Quercus ilex; resprouting

¿Puede la gestión forestal mitigar los efectos de un incremento de sequía en los montes mediterráneos? El caso de los bosques de encina y roble en el contexto del cambio climático. - COTILLAS, M; ESPELTA, J M; Sabate, S (V Congreso Forestal Español, 2009)
Uno de los grandes retos para la conservación de los ecosistemas forestales a lo largo del presente siglo es el cambio climático, del que se esperan importantes repercusiones en la cuenca mediterránea. Los modelos climáticos proyectan para esta área un descenso en la precipitación que, unido a un aumento de las temperaturas, acrecentará la ya de por sí característica sequía estacional que caracteriza esta zona. Dadas estas proyecciones, se hace necesario determinar los efectos que tendría una reducción de la precipitación en las diferentes especies que componen nuestros bosques, para poder así estimar posibles cambios en la estructura y composición de los mismos e identificar estrategias de gestión adecuadas para mitigar su efecto. En este contexto, el objetivo de nuestro estudio es analizar los efectos de una reducción de la precipitación en el monte bajo de encina (Quercus ilex L.) y roble (Quercus cerrioides Willk & Costa), así como evaluar los efectos de la gestión (resalveo) en su respuesta a este. Para ello, se combinan en un bosque mixto dos niveles de precipitación (precipitación natural vs. reducción de la precipitación de un 15%) y gestión (no gestión vs. gestión) en cuatro tratamientos. Se analiza la mortalidad, crecimiento, nueva rebrotada y dinámica foliar. Tras cuatro años de seguimiento el experimento sigue en curso, y hasta ahora se han obtenido los resultados definitivos de mortalidad, crecimiento y nueva rebrotada, que muestran que: i) La gestión reduce fuertemente la mortalidad, ii) El crecimiento de los robles se ve notablemente afectado por la reducción de precipitación, mientras que el de las encinas permanece constante, iii) La gestión incrementa fuertemente el crecimiento en ambas especies, especialmente en condiciones de precipitación natural. Actualmente se están comenzando a analizar los datos de dinámica foliar, y los resultados preliminares muestran que iv) Las parcelas sometidas a reducción de precipitación presentan un número menor de hojas, una menor longevidad de las mismas, y una mayor tasa de caída de hojarasca que las no sometidas a este tratamiento, v) La gestión atenúa la caída de hojas en todas las parcelas, mitigando los efectos de la reducción de precipitación en las parcelas sometidas a este tratamiento. De estos resultados se extrae la conclusión de que el cambio climático puede tener consecuencias negativas sobre los bosques de Quercus mediterráneos, siendo más acusados los efectos en robles caducifolios. Sin embargo, la gestión forestal puede ser una potente herramienta para mitigar estos efectos y conservar nuestros bosques de cara al futuro.
Keywords: cambio climático; Quercus cerrioides; Quercus ilex; resalveo; sequía

Differences in biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) result in similar performance of seedlings of two Mediterranean oaks with contrasting leaf habit - Espelta, Josep Maria; Cortés, Pilar; Mangirón, Marta Retana, Javier (Ecoscience, 2005)
Co-occurrence of winter-deciduous and evergreen oaks is common in some Mediterranean-type climate areas. However, whether these species show an overlap in their regeneration niche is still poorly understood. We explored experimentally the changes in survival, growth, biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) in seedlings of a deciduous oak (Quercus cerrioides) and an evergreen oak (Quercus ilex) in response to co-variation in light and water availability. Quercus cerrioides exhibited higher root length, root area, leaf nitrogen content, and less negative δ13C, but lower leafiness than Q. ilex. The interaction between species and light in specific leaf area and root–shoot ratio indicated different mechanisms to overcome water stress in the two oaks, with Q. ilex relying on leaf hardening and Q. cerrioides relying on a high root–shoot ratio. However, the two species showed similar survival and growth in most of the light–water gradient. Ecological inference of these results indicates that seedlings of these species have a similar ability to cope with variations in light and water in spite of their contrasting leaf habit. This similar performance suggests a competition for similar micro-sites during establishment, rather than a partitioning of the regeneration niche.
Keywords: deciduous; evergreen; Mediterranean-type climate; Quercus cerrioides; Quercus ilex; Regeneration

Differences in biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) result in similar performance of seedlings of two Mediterranean oaks with contrasting leaf habit - Espelta, Josep Maria; Cortés, Pilar; Mangirón, Marta Retana (Ecoscience, 2005)
Co-occurrence of winter-deciduous and evergreen oaks is common in some Mediterranean-type climate areas. However, whether these species show an overlap in their regeneration niche is still poorly understood. We explored experimentally the changes in survival, growth, biomass partitioning, leaf nitrogen content, and water use efficiency (δ13C) in seedlings of a deciduous oak (Quercus cerrioides) and an evergreen oak (Quercus ilex) in response to co-variation in light and water availability. Quercus cerrioides exhibited higher root length, root area, leaf nitrogen content, and less negative δ13C, but lower leafiness than Q. ilex. The interaction between species and light in specific leaf area and root–shoot ratio indicated different mechanisms to overcome water stress in the two oaks, with Q. ilex relying on leaf hardening and Q. cerrioides relying on a high root–shoot ratio. However, the two species showed similar survival and growth in most of the light–water gradient. Ecological inference of these results indicates that seedlings of these species have a similar ability to cope with variations in light and water in spite of their contrasting leaf habit. This similar performance suggests a competition for similar micro-sites during establishment, rather than a partitioning of the regeneration niche.
Keywords: deciduous; evergreen; Mediterranean-type climate; Quercus cerrioides; Quercus ilex; Regeneration

Effects of a nursery CO 2 enriched atmosphere on the germination and seedling morphology of two Mediterranean oaks with contrasting leaf habit - Cortés, Pilar; Espelta, J. M.; Save, Robert; Biel, C. (New Forests, 2004)
The use of an enriched CO2 atmosphere in tree nurseries has been envisaged as a promising technique to increase productivity and to obtain seedlings with a higher root/shoot ratio, an essential trait to respond to water stress in Mediterranean-type ecosystems. In that framework, we have analyzed the effects of three levels of atmospheric CO2 concentration (350, 500 and 700 ppm) on the germination rate, growth and morphology of seedlings of two Mediterranean oaks used in reforestation programs: the evergreen Quercus ilex L. and the deciduous Quercus cerrioides Wilk. et Costa. CO2 enrichment increased the germination rate of Q. cerrioides (from 70 7 to 81 3%) while it decreased that of Q. ilex (from 71 10 to 41 12%). Seedlings of both species increased approximately 60% their total biomass in response to CO2 enrichment but at two different CO2 concentrations: 500 ppm for Q. cerrioides and 700 ppm for Q. ilex. This increase in seedlings biomass was entirely due to an augmentation of root biomass. Considering germination and biomass partitioning, an enriched CO2 atmosphere might not be appropriate for growing Mediterranean evergreen oaks, such as Q. ilex, since it reduces acorn germination and the only gains in root biomass occur at a high concentration (700 ppm). On the other hand, a moderate CO2 enrichment (500 ppm) appears as a promising nursery technique to stimulate the germination, growth and root/shoot ratio of deciduous oaks, such as Q. cerrioides
Keywords: Forest restoration; Mediterranean-type ecosystems; Nursery techniques; Quercus cerrioides; Quercus ilex; Wildﬁre

Effects of a nursery CO 2 enriched atmosphere on the germination and seedling morphology of two Mediterranean oaks with contrasting leaf habit - Cortés, Pilar; ESPELTA, J M; Save, Robert; Biel, C (New Forests, 2004)
The use of an enriched CO2 atmosphere in tree nurseries has been envisaged as a promising technique to increase productivity and to obtain seedlings with a higher root/shoot ratio, an essential trait to respond to water stress in Mediterranean-type ecosystems. In that framework, we have analyzed the effects of three levels of atmospheric CO2 concentration (350, 500 and 700 ppm) on the germination rate, growth and morphology of seedlings of two Mediterranean oaks used in reforestation programs: the evergreen Quercus ilex L. and the deciduous Quercus cerrioides Wilk. et Costa. CO2 enrichment increased the germination rate of Q. cerrioides (from 70 7 to 81 3%) while it decreased that of Q. ilex (from 71 10 to 41 12%). Seedlings of both species increased approximately 60% their total biomass in response to CO2 enrichment but at two different CO2 concentrations: 500 ppm for Q. cerrioides and 700 ppm for Q. ilex. This increase in seedlings biomass was entirely due to an augmentation of root biomass. Considering germination and biomass partitioning, an enriched CO2 atmosphere might not be appropriate for growing Mediterranean evergreen oaks, such as Q. ilex, since it reduces acorn germination and the only gains in root biomass occur at a high concentration (700 ppm). On the other hand, a moderate CO2 enrichment (500 ppm) appears as a promising nursery technique to stimulate the germination, growth and root/shoot ratio of deciduous oaks, such as Q. cerrioides
Keywords: Forest restoration; Mediterranean-type ecosystems; Nursery techniques; Quercus cerrioides; Quercus ilex; Wildﬁre